Salivary secretory immunoglobulin A reactivity: a comparison to cortisol and α-amylase patterns in the same breast cancer survivors - Lambert, Maude (Contemp Oncol (Pozn), 2018)
INTRODUCTION: One way to examine the extent to which the stress associated with a breast cancer experience (BC) impacts stress-related physiological mechanisms is to study the secretion patterns of associated biomarkers. Unlike cortisol and α-amylase (sAA), biomarkers of immune functioning such as secretory immunoglobulin A (SIgA) have rarely been examined in BC survivors. AIM OF THE STUDY: This study had two principal aims: the first was to evaluate the basal secretion profiles of SIgA as well as its response to an acute stressor as a marker of immune health in BC survivors and women with no history of BC, and the second was to determine how SIgA stress-related patterns compare to published cortisol and sAA patterns in the same women. RESULTS: Overall, the findings indicate that BC survivors exhibit a blunted cortisol reaction to an acute stressor, a generally elevated diurnal sAA concentration pattern, and normal SIgA profiles, compared to women with no history of cancer. This study serves as a foundation for future research to elucidate the relationships between BC experience variables, stress biomarkers, and health outcomes in BC survivors.